The binuclear cyclopalladated complex CP2 is targeting ubiquinol-cytochrome c reductase (complex III) of Leishmania amazonensis - Arenas Velásquez, Angela Maria [UNESP]; Patino Linares, Irwin Alexander; Gaspers, Lawrence D.; Bartlett, Paula J.; Velasques, Jecika M. [UNESP]; Netto, Adelino V.G. [UNESP]; Thomas, Andrew P.; Graminha, Marcia A.S. [UNESP] (Elsevier, 2025)
Leishmaniasis is a neglected disease that remains with a limited number of drugs available for chemotherapy and has an increased drug resistance that affects treatment outcomes. Metal-based drugs such as cyclopalladated complex [Pd(dmba)(μ-N3)]2 (CP2), a Leishmania topoisomerase IB inhibitor involved in calcium dysregulation and mitochondrial dysfunction of the parasite, had been an alternative to outline the appearance of chemoresistance. To identify new molecular targets and point out possible resistance mechanisms, a CP2-resistant Leishmania amazonensis (LaR) was selected by stepwise exposure to increasing drug pressure until a line capable of growth in 13.3 μM CP2. LaR IC50 value was 52.4 μM (4-fold higher than L. amazonensis–wild type, La). LaR promastigotes were cross-resistant to other DNA topoisomerase I inhibitors (camptothecin) and more susceptible to anti-leishmanial drugs pentamidine and miltefosine. A protective effect on cell viability was observed by pretreating the parasite with Ca2+ channel blockers followed by CP2 in La but not in LaR. Analyses of the cell viability of La and LaR using electron transport chain (ETC) inhibitors demonstrated that La is more sensitive than LaR. The studies of mitochondrial oxygen consumption demonstrated that LaR is less susceptible to complex III (ubiquinol-cytochrome c reductase – CcR) inhibitor, antimycin A (AA). CcR activities of La and LaR were equal for both strains in the absence of CP2 and significantly decreased, 69 % for La and 51 % for LaR, in the presence of CP2. This resistance is attributed to overexpression of CcR, confirmed by the RT-qPCR. CcR inhibition by CP2 leads the parasite to increase the reactive oxygen species (ROS) production, principally in La. Therefore, in this work, we suggested that CcR is the main target of CP2 in the mitochondria, acting to inhibit mitochondria respiratory, and the LaR mutant has increased activity of CcR, which reduces the formation of ROS.
Keywords: Anti-leishmanial drug; Calcium channel blockers; Cyclopalladated complex; Electron transport chain; Leishmania amazonensis; Mitochondrial calcium uniporter; Mitochondrial oxygen consumption; Ubiquinol-cytochrome c reductase